(untitled) (Third Sector Social Economic Review, 2023)
The rapidly growing and developing industrial sector has made forming organized industrial zones inevitable. Organized industrial zones have an important role as centers of economic growth, industrial production and employment. However, intensive industrial activities bring various environmental, economic and social risks. Challenging factors such as natural disasters, climate change and industrial accidents can expose organized industrial zones to serious threats. The recent global Covid-19 pandemic and the Kahramanmaraş-based earthquakes in Turkey have once again reminded us of the potentially destructive impact of the natural environment. This study aims to reveal the current situation of organized industrial zones in the context of disaster preparedness and resilience and to make some recommendations. For this purpose, interviews were conducted with OIZ managers in Çankırı province. In this context, the information on the extent to which disaster management and resilience measures are included in the strategic planning of organized industrial zones, how effectively they are implemented, and what level of preparedness is provided against possible risks were evaluated by descriptive content analysis. The results of the analysis show that there are three dimensions of resilience and sustainability for organized industrial zones. These are (I) internal preparation, (ii) collaborations with external stakeholders, and (iii) planning and legal regulations of the upper institutions. In this context, organized industrial zones should make risk analyzes, create emergency plans and raise awareness against disasters by involving all their internal and external stakeholders in cooperation.